The hype handbook : 12 indispensable success secrets from the world's greatest propagandists, self-promoters, cult leaders, mischief makers, and boundary breakers - Schein, Michael (Author of The hype handbook) (McGraw-Hill, 2021)
"Ingenious strategies and tips for leveraging shameless propaganda for personal and social good Hype runs the world. Rarely in history have people been so susceptible to propaganda and manipulative messaging-and those who have perfected the art and science of hype are coming out on top. Imagine if you could generate and leverage hype with such mastery-only for good purposes, like legitimate business success. You can! In The Hype Handbook, marketing guru Michael Schein provides 12 fundamental strategies for creating and leveraging hype for good. This truly unique guide breaks the concept of hype down into a simple set of objective strategies, skills, and techniques. Schein combines stories from the world's most effective hype artists-like American propagandist Edward Bernays, Alice Cooper manager Shep Gordon, celebrity preacher Aimee Semple McPherson, Spartan Race founder Joe De Sena, and digital guru Gary Vaynerchuk-with the latest research in psychology, sociology and neuroscience. Regardless of your temperament, budget, background, or level of natural ability, The Hype Handbook delivers everything you need to apply the most powerful tool of persuasion for personal and business success"--